Comparing Chinese and US practitioners' attitudes towards teletherapy during the COVID‐19 pandemic. (27th October 2020) - Wang, Xiubing; Gordon, Robert M.; Snyder, Elise W.
Abstract: Introduction: The China American Psychoanalytic Alliance (CAPA) has been offering psychoanalytic psychotherapy training and treatment to Chinese mental health professionals entirely over the Internet since 2006. When the COVID‐19 pandemic began, most practitioners worldwide had to turn to teletherapy. US psychoanalytic practitioners were more negative towards teletherapy than those from other theoretical orientations. We predicted that CAPA practitioners as compared to US psychoanalytic practitioners would be more prepared for teletherapy services during the pandemic, since they their training and treatment had been on‐line. Method: We compared survey results from 164 CAPA practitioners with 165 US psychoanalytic practitioners (matched for age) who had recently psychoanalytically treated a patient on‐line. CAPA participants were recruited from CAPA email lists and the US sample were recruited from the Society for Psychoanalysis and Psychoanalytic Psychology of the American Psychological Association, the American Psychoanalytic Association and International Psychotherapy Institute. Results: CAPA practitioners as compared to US psychoanalytic practitioners had more positive opinions about teletherapy before the pandemic; had more positive opinions about teletherapy during the pandemic; and had more positive opinions about the effectiveness of teletherapy in working with transference, relational issues and resistance. The CAPA practitioners were more prepared to do psychoanalytic psychotherapy during the pandemic than the US psychoanalytic practitioners. Discussion: Xiubing Wang discusses these findings in terms of her own experience as a CAPA graduate and treater before, during and after the COVID‐19 pandemic in China.